Current and emerging strategies for the treatment of acute pericarditis: a systematic review - Samar Sheth; Dee Dee Wang; Christos Kasapis (Dove Medical Press, 2010)
Samar Sheth1, Dee Dee Wang3, Christos Kasapis21Department of Internal Medicine, 2Division of Cardiovascular Medicine, University of Michigan, Ann Arbor, MI, USA; 3Henry Ford Hospital, Division of Cardiovascular Medicine, Detroit, MI, USAAbstract: Pericarditis is a common disorder that has multiple causes and presents in various primary-care and secondary-care settings. It is diagnosed in 0.1% of all hospital admissions and in 5% of emergency room visits for chest pain. Despite the advance of new diagnostic techniques, pericarditis is most commonly idiopathic, and radiation therapy, cardiac surgery, and percutaneous procedures have become important causes. Pericarditis is frequently benign and self-limiting. Nonsteroidal anti-inflammatory agents remain the first-line treatment for uncomplicated cases. Integrated use of new imaging methods facilitates accurate detection and management of complications such as pericardial effusion or constriction. In this article, we perform a systematic review on the etiology, clinical presentation, diagnostic evaluation, and management of acute pericarditis. We summarize current evidence on contemporary and emerging treatment strategies.Keywords: pericarditis, pericardial disease, treatment strategies